2015
DOI: 10.1021/jf505694e
|View full text |Cite
|
Sign up to set email alerts
|

Zein-Based Nanoparticles Improve the Oral Bioavailability of Resveratrol and Its Anti-inflammatory Effects in a Mouse Model of Endotoxic Shock

Abstract: 27Resveratrol offers pleiotropic health beneficial effects including its reported capability to 28 inhibit lipopolysaccharide (LPS) induced cytokine production. The aim of this work was 29 to prepare, characterize and evaluate a resveratrol nanoparticulate formulation based 30 on zein. For this purpose the oral bioavailability of the encapsulated polyphenol as well 31 as its anti-inflammatory effect in a mouse model of endotoxic shock were studied. 32Resveratrol-loaded nanoparticles displayed sizes around 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(86 citation statements)
references
References 45 publications
4
80
0
Order By: Relevance
“…These observations suggest that sometimes lower dose of diet-derived agents are more effective than higher doses to prevent cancer. These results emphasize the need to perform a dose response studies and develop better methods to deliver diet-derived chemopreventive molecules such as resveratrol reach the target tissues by using modern technologies such as microencapsulation or nanoparticles(57,58) to derive their beneficial actions. after warm ischemia and reperfusion in rat liver.…”
mentioning
confidence: 94%
“…These observations suggest that sometimes lower dose of diet-derived agents are more effective than higher doses to prevent cancer. These results emphasize the need to perform a dose response studies and develop better methods to deliver diet-derived chemopreventive molecules such as resveratrol reach the target tissues by using modern technologies such as microencapsulation or nanoparticles(57,58) to derive their beneficial actions. after warm ischemia and reperfusion in rat liver.…”
mentioning
confidence: 94%
“…9,10) Additionally, resveratrol has been shown to be capable of inhibiting lipopolysaccharide (LPS) induced inflammatory response. 11,12) A lot of preclinical findings have demonstrated that resveratrol is well tolerated and non-toxic. 13) It has been reported that gastric toxicity of NSAIDs are largely dependent on the presence of the carboxylic group, 14) therefore, NSAIDs esterified with resveratrol may be a new approach to retaining anti-inflammatory properties while reducing side effects.…”
mentioning
confidence: 99%
“…Oral administration of resveratrol formulated in a zein‐protein nanoparticle increased the oral bioavailability compared to resveratrol solution, reduced rectal temperature and reduced serum TNFα levels in the LPS‐induced endotoxic shock mouse model (Penalva et al . ).…”
Section: Disease States and The Intestinal Barriermentioning
confidence: 97%